The arms race in bacteria-phage interaction: deciphering bacteria defense and phage anti-defense mechanisms through metagenomics - Zhang, Siyuan; Chu, Mengqi; Sun, Xumei (Frontiers in Microbiology, 2025)
Bacteriophages are viruses that specifically infect bacteria and co-evolve with their hosts through mutual interactions. They represent one of the most significant drivers of microbial diversity, influencing its evolution, generation, and maintenance. To counter bacteriophage infection, bacteria have developed sophisticated immune systems, including both passive adaptations, such as inhibiting phage adsorption and preventing DNA entry, and active defense systems such as restriction-modification systems and CRISPR-Cas systems. The ongoing arms race between bacteriophages and bacteria has left distinct evolutionary signatures in their genomic sequences. Advances in large-scale genomic and metagenomic sequencing technologies, coupled with bioinformatics approaches, have greatly enhanced our understanding of bacteria-phage interaction mechanisms, driving progress in bacteriophage biology. This review systematically analyses the diverse immune strategies bacteria employ against phage infection, elucidates the coordination and interrelationships among different anti-phage mechanisms, and highlights potential directions for future research.